Pondasi Dangkal diatas Tanah Lunak dengan Perkuatan Cerucuk Galam Berdasarkan Percobaan Lapangan - Yusti Yudiawati; Ahmad Marzuki (Universitas Lambung Mangkurat, 2008)
This research studying the behaviour of shallow foundation with cerucuk support. 1,0 m2 reinforced concrete square of shallow foundation model is used, with 5 cm of cerucuk diameter. The research is to find out the foundation ultimate bearing capacity with 1,0 m and 2,0 m length variety of cerucuk, the distance between the pile is 1/4B, 1/3B and 1/2B and also area covered with cerucuk is 1,0 m2, 2,0 m2 and 3,0 m2. To observe the settlement behaviour is made with giving fixed load of 40%, 60% and 100% of ultimate load ratio at 1,0 m and 2,0 m cerucuk at the same area covered with cerucuk that is 2,0 m2. The result of research shows that the deeper the cerucuk is embedded, the distance between the pile is getting closer and the wider the area covered with cerucuk, the pile ultimate bearing capacity is bigger and the settlement is smaller. To decrease the settlement of shallow foundation, the fixed load that allowable must be < 40 % of ultimate load and Safety Factor must be > 2,5.